Productive performance and ruminal development in dairy kids fed with different diets and slaughtered at different ages. (FAVE Sección Ciencias Veterinarias, 2019)
The aim of this work was to evaluate performance and ruminal development of dairy kids fed with different diets (alfalfa and / or grains: Alf, Alf + Gr, Gr) and slaughtered at different ages (50, 60 and 70 days of life). Parameters evaluated were: daily live weight gain (GDPV), slaughter weight (PF), hot carcass weight (PCC), slaughter yield (RF), stomach weight and ruminal papillae length (LP). Animals were assigned by random in the treatments: Alf 50 (n=3), Alf 60 (n=4), Alf 70 (n=3), Gr 50 (n=3), Gr 60 (n=4), Gr 70 (n=3), Alf+Gr 50 (n=3), Alf+Gr 60 (n=4), Alf+Gr 70 (n=3). Data were analyzed with linear mixed model according to a repeated measures design by ANOVA of Infostat 2018 program. Means multiple comparisons were evaluated by LSD-Fisher test (P = 0.05). No interaction was detected for diet and slaughter age. Regarding diet, animals that consumed Alf and Alf + Gr presented higher GDPV (p = 0.0022).  FP and PCC were higher for Alf + Gr than for Gr group (p = 0.0352 and p = 0.0298). RF was higher for the Gr group than for the others (p
Keywords: goat; production; feed; dairy